Phytochemical Analysis, Antioxidant Activity of Wild Medicinal Plants of Himalayan Range - Sarwade, Prakash Pralhad; Nisha, K Barakkath; Hari, Irrusappan; Tawale, Hemant; Ambika, J.; Thaiyalnayagi, S.; Yadav, Madhulika Krishan; (Sarwade), Kavita Narayan Gaisamudre; Geetha, M. (Journal for Research in Applied Sciences and Biotechnology, 2024)
Plants that are indigenous to the Himalayas have been exploited for their therapeutic properties for over 6,500 years. Using their deep knowledge of the local flora and fauna, traditional healers in the region are able to treat a wide variety of maladies with herbal treatments. People who live in rural areas of the Himalayas rely on wild medicinal plants for their health, and we need to do everything in our power to ensure that these plants continue to thrive in the harsh desert climate of the Himalayas. Raw materials that are obtained from wild plants are in high demand all around the world, particularly among pharmaceutical companies, ethnomedics, and practitioners of traditional medicine as well as other medical practitioners. India has been a top exporter of raw herbal medications all over the world. This is mostly due to the number of medicinal plants that can be found in the Himalayas. The aim of this study was to determine the Phytochemical analysis and antioxidant activity of various parts of 20 selected wild medicinal plants, found in the Himalayan regions in India, China, Nepal, Bhutan and Pakistan including Swertia bimaculate, Ficus neriifolia, Rubus treutleri, Periploca calophylla, G. depressa, Buddleja napaulensis, Habenaria edgeworthii, Pyracantha crenulate, Roscoea procera, Allium rubellum, Berberis chitria, Capsella bursa-pastoris, Artemisia maritima, C. glanduliferum, C. distans, Juniperus macropoda, Origanum vulgare, Valeriana jatamansi, Polygonatum verticillatum, Meconopsis aculeate and Fragaria nubicolais. There were several different parts of the species that were examined to determine their total polyphenol, flavonoid, alkaloid, saponin, and tannin concentrations. One fraction of the plant extracts was found to contain a higher quantity of phytochemicals when compared to the other portions. Through the utilisation of the DPPH and FRAP model systems, the antioxidant capacity of a number of different components was assessed. The high-performance liquid chromatography (HPLC) technique can be combined with the DPPH and/or ABTS tests in order to rapidly screen extracts for the presence of active chemicals.